Study on the experiment and reaction kinetics of sulfur removal from coal by microorganisms - Zhao, Dan; Sun, Ping-ping; Ai, Chun-ming; Mu, Xiao-zhi (Frontiers in Microbiology, 2023)
Abstract: To solve the safety problem of spontaneous combustion of high-sulfur coal, applied microbiology, physical chemistry, reaction kinetics theory, combined with the SEM, FTIR and TG-DTG-DSC experiments and analysis of testing methods, the microbial desulfurization experiments were carried out, and the change law of the desulfurization reaction of coal before and after the element composition, main physical and chemical properties, the coal spontaneous combustion point was studied. The results show that when the temperature is 30°C, the coal particle size is 120 mesh, the initial pH value is 2.0 and the bacteria liquid amount is 15ml, the desulfurization effect of the coal sample is the best, and the maximum desulfurization rate can reach 75.12%. There is obvious erosion on the surface of the coal sample after microbial desulfurization, the pyrite in the coal is obviously reduced, and the molecular structure in the coal is basically unchanged. Under the action of microorganism, part of inorganic sulfur in coal is removed, the spontaneous combustion point of coal is increased by 50°C, the activation energy of coal has increased more than three times, and the possibility of spontaneous combustion of coal is reduced. By analyzing the reaction kinetics of the microbial desulfurization process, it can be seen that the microbial desulfurization reaction is controlled by external diffusion, internal diffusion and chemical reaction, among which internal diffusion is the main influencing factor.